Analisis Nisbah Bagi Hasil Produk Deposito Mudharabah Dalam Lembaga Keuangan Syariah - Nursiah, Ayu; Sari, Bela Nopita; Firdausi, Dian Raudatul; Ria, Dina Yovita; Syarif, Ahmad Hazas (As-Syirkah: Islamic Economic & Financial Journal, 2022)
Profit  sharing  is  profit  sharing  system  in  wich  the  owner  of  the  capital coorporate with the owner of the capital to carry out business activities.if the business activity generates a profit, it is shared by both and when it experiences a loss it is borne together as well. Sharia banking introduced a system to the public with the term Revenue Sharing,  which  is  a  profit  sharing  system  that  is  calculated  from  the  total  fund management revenue without deducting the cost of managing funds. The concept of profit sharing aims as follows: (a). The owner of the funds will invest their funds through an Islamic financial institution that acts as the manager. (b). The sharia financial manager or institution will manage the funds in a pool of funds system and will then invest the funds into a viable and profitable project or business that meets the aspects of sharia. (c). Both parties sign a contract wich contains the scope of the cooperation, nominal, ratio and time period for the agreement. In this study, qualitative methods are used. The results of this research are use the result of this research are coorperation in profit sharing in banking product, especialy in mudharbah deposit product. So the profit sharing ratio in mudarabh products can be conlueded that the profits abotained are divided according to the agreed ratio.